Experience of labor migration in the EU and the possibility of its application in the EAEU (Journal of actual problems of jurisprudence, 2021)
The article is based on the legislative and practical analysis of the long-term experience of the European Union and the possibility of applying this best practice to protect the rights and freedoms of workers in the framework of the Eurasian Economic Union. In a comparative analysis of the character- istics of these two territorial unions, we could not lose sight of the activities of international universal organizations.The purpose of the article is to identify problems and solutions through a comprehensive study of the EU programs and regulations governing labor migration, as well as the legal aspects that can be applied in the Eurasian Economic Union.The scientific and practical value of this article is to propose for the first time new legal mechanisms within the framework of the Eurasian Economic Union, to illustrate the experience of international organizations and associations, unions with many years of international experience in the field of labor rights protection.Using the comparative legal method, the experience of the EU was revealed, which can be used within the EAEU. The historical legal method set the goal of creating the EAEU and its role for working people of the EAEU.The EAEU, based on the experience of the EU, offers effective ways to regulate the rights of workers. In particular, they considered the possibility of forming customs and traditions, strengthening territorial agreements, and providing benefits to employees in third countries.